Annealing temperature controlled crystallization mechanism and properties of gallium oxide film in forming gas atmosphere. Issue 6 (7th March 2022) - Wang, Chen; Li, Shi‐Wei; Fan, Wei‐Hang; Zhang, Yu‐Chao; Lin, Hai‐Jun; Zhang, Xiao‐Ying; Lien, Shui‐Yang; Zhu, Wen‐Zhang; Wuu, Dong‐Sing
Abstract: Gallium oxide (Ga2 O3 ) films had been fabricated on Al2 O3 (0001) substrate by employing pulsed laser deposition (PLD) and annealed at different temperatures under forming gas (FG) atmosphere (95% N2 + 5% H2 ). The influence of annealing temperature on the structural, optical, chemical composition, and surface morphological properties of the Ga2 O3 thin films was investigated comprehensively. The annealing processes with hydrogen gas play a crucial role in the characteristics of Ga2 O3 thin films. A crystallization mechanism of Ga2 O3 films controlled by annealing temperature has been proposed firstly and analyzed systematically, which contains three kinds of competitive mechanism, namely the thermal enhanced crystallization, the enhanced H2 dissociative adsorption on Ga2 O3 surfaces, and the high‐temperature decomposition of Ga2 O3 . Both Ga + and Ga 3+ oxidation valence states were presented in all samples, which indicated lattice oxygen deficiency in Ga2 O3 films. The variation of the non‐lattice oxygen proportion of Ga2 O3 films related to the crystallization mechanism firstly increased and then decreased with the increase of annealing temperature. The detailed crystallization mechanism of PLD‐Ga2 O3 films annealed in FG offers a guideline and references for the further fabrication of high‐quality Ga2 O3 films and their applications in high‐performance devices.